Adhesive Wear Behavior of Heat Treated Spheroidal Graphite Cast Iron. Issue 1 (19th February 2015) - Salim, M; Shama, S; Mozumder, Y H; Behera, R K; P, Sindhoora L; Pattanaik, A; Mishra, S C; Sen, S
Abstract: Spheroidal graphite cast iron is one of the most favorable materials in cast iron family due to its wide range of mechanical and tribological properties. In the current research priority is given towards the investigation of wear system response of spheroidal graphite cast iron subjected to various heat treatment conditions. Pearlitic/ferritic and upper bainitic matrix was obtained through normalizing and austempering treatment for an austenitizing temperature of 1000°C. Dry sliding wear test was performed at 10N, 20N, 30N for a sliding distance of 7.54m. With increase in load weight loss was observed for as-cast specimen whereas normalized specimen showed very less weight loss with increasing load. On the other hand the austempered specimen observed to lose weight when operated at 10N, whereas at 20N and 30N drastic gain in weight was observed.